A Combinatorial Vaccine Containing Inactivated Bacterin and Subunits Provides Protection Against Actinobacillus pleuropneumoniae Infection in Mice and Pigs - Zhang, Lijun; Luo, Wentao; Xiong, Ruyue; Li, Haotian; Yao, Zhiming; Zhuo, Wenxiao; Zou, Geng; Huang, Qi; Zhou, Rui (Frontiers in Veterinary Science, 2022)
Actinobacillus pleuropneumoniae (APP) is the etiological agent of porcine contagious pleuropneumonia (PCP) that causes great economic losses in the swine industry. Currently, vaccination is still a commonly used strategy for the prevention of the disease. Commercially available vaccines of this disease, including inactivated bacterins and subunit vaccines, have clinical limitations such as side effects and low cross-protection. In this study, a combinatorial vaccine (Bac-sub) was developed, which contained inactivated bacterial cells of a serovar 1 strain and three recombinant protoxins (rApxIA, rApxIIA, and rApxIIIA). Its side effects, immune protection, and cross-protection were evaluated and compared with a commercial subunit vaccine and a commercial trivalent bacterin in a mouse infection model. The results revealed that the Bac-sub vaccine showed no obvious side effects, and induced higher levels of Apx toxin-specific IgG, IgG1, and IgG2a than the commercial vaccines after booster. After a challenge with virulent strains of serovars 1, 5, and 7, the Bac-sub vaccine provided greater protection (91.76%, 100%, and 100%, respectively) than commercial vaccines. Much lower lung bacterial loads (LBLs) and milder lung lesions were observed in the Bac-sub-vaccinated mice than in those vaccinated with the other two vaccines. The protective efficacy of the Bac-sub vaccine was further evaluated in pigs, which showed that vaccinated pigs displayed significantly milder clinical symptoms and lung lesions than the unvaccinated pigs after the challenge. Taken together, Bac-sub is a safe and effective vaccine that could provide high protection against A. pleuropneumoniae infection in both mice and pigs.